Overexpression of LtKNOX1 from Lilium tsingtauense in Nicotiana benthamiana affects the development of leaf morphology - Rui Zhou; Menglong Fan; Mei Zhao; Xinqiang Jiang; Qinghua Liu (Plant Signaling & Behavior, 2022)
Leaves are the main vegetative organs of the aboveground part of plants and play an important role in plant morphogenesis. KNOTTED-LIKE HOMEOBOX (KNOX) plays a crucial role in regulating leaf cell fate and maintaining leaf development. In this study, we analyzed LtKNOX1 from Lilium tsingtauense and illustrated its function in transgenic plants. Tissue-specific expression analysis indicated that LtKNOX1 was highly expressed in stems, young flower buds, and shoot apical meristems (SAMs). Ectopic overexpression of LtKNOX1 in Nicotiana benthamiana suggested that transformants with mild phenotypes were characterized by foliar wrinkles and mildly curled leaves; transformants with intermediate phenotypes showed severely crimped blades and narrow leaf angles, and the most severe phenotypes lacked normal SAMs and leaves. Moreover, the expression levels of genes involved in the regulation of KNOX in transgenic plants were detected, including ASYMMETRIC LEAVES1, PIN-FORMED 1, GA20-oxidase, CUP-SHAPED COTYLEDON 2, CLAVATA 1 and WUSCHEL(WUS), and the expression of other genes were down-regulated except WUS. This study contributes to our understanding of the LtKNOX1 function.